OP0090 Determinants of Survival of Fetuses with Autoimmune Congenital Heart Block and Factors Associated with Neonatal and Late-Onset Dilated Cardiomyopathy: 214 Cases from the French Registry of Neonatal Lupus. (9th June 2015) - Lévesque, K.; Morel, N.; Maltret, A.; Baron, G.; Hamidou, M.; Orquevaux, P.; Piette, J.-C.; Barriere, F.; Lebidois, J.; Fermont, L.; Fain, O.; Theulin, A.; et al.
Abstract : Background: Neonatal lupus syndrome (NLS) includes congenital heart block (CHB) and cardiomyopathies. Its optimal management is debated. Objectives: We analyzed the mortality and morbidity of CHB, with special focus on risk factors. Methods: This was a retrospective study of the French national registry of NLS. Inclusion criteria were high-degree CHB associated with maternal anti-SSA/SSB antibodies. Results: 214 CHB were included (202 in utero cases and 12 neonatal cases). These 214 fetuses or children were born to 195 mothers anti-SSA (99.5%) and/or anti-SSB antibodies (60%) positive. 51 mothers (26.2%) fulfilled the classification criteria for an autoimmune disease: systemic lupus erythematosus (n=23), Sjögren syndrome (n=14), undifferentiated connective tissue disease (n=7), or other autoimmune disease (n=7). The factors associated with feto-neonatal deaths (15.7%) were hydrops (p<0.001; HR: 12.4 [95%CI: 4.7-32.7]) and prematurity (p=0.002; HR: 17.1 [95%CI: 2.8-103.1]). During a median follow-up of 7 years [birth to 36.1 years], 148 of 187 surviving children (79.1%) had a pacemaker, 35 (18.8%, one missing data) had dilated cardiomyopathy (DCM), and 22 (11.8%) died. DCM was neonatal (n=13) or late-onset (n=22, diagnosed at a median age of 15.2 months [3.6 months-22.8 years]). Factors associated with neonatal DCM were maternal treatment with hydroxychloroquine, in utero cardiomegaly, in utero DCM, and hydrops. By contrast, only non-white race origin and significant in utero valvulopathy were associated with late-onset DCM. On multivariate analysis, only in utero DCM was associated with neonatal DCM (p=0.0001; HR 15.99 [95%CI: 3.93-65.01]), whereas non-white race origin was associated with late-onset DCM (p=0.0147; HR 3.65 [95%CI: 1.28-10.0]). For children who survived the neonatal period (n=179), the risk of death during follow-up was 7.8%. On multivariate analysis, the only factor associated with late mortality was postnatal DCM (neonatal and late-onset DCM) (p<0.0001; HR 36.48 [95% CI 8.11-164.13]). The probability of survival at 10 years of age for a child with CHB born alive was 87.1%: 23.1% in the presence of neonatal DCM, 53.9% for those who developed a late-onset DCM requiring treatment versus 98.6% in those without DCM. Fluorinated steroid in utero treatment was not associated with CHB regression, survival or absence of late-onset DCM. Conclusions: The factors associated with late-onset DCM differ completely from those associated with neonatal DCM. Our findings do not support the use of fluorinated steroids for CHB. Disclosure of Interest: None declared